Agricultural vulnerability to changing rainfall patterns: Assessing the role of smallholder farmers’ perceptions and access to weather forecast information in adaptation-decision making - Muyiramye, Didier (2020)
Adverse weather is currently among the crucial challenges facing agricultural development in sub-Saharan Africa. With climate change and variability increasing, rainy seasons are becoming more and more unpredictable. Heavy rainfalls and severe flooding have increased, affecting smallholder farming and rural livelihoods considerably. Using qualitative and quantitative methods in data collection, this study aimed at exploring climate change adaptation strategies in North-Western Rwanda, by assessing the role of smallholder farmers’ perceptions on the vulnerability of their farming to changing rainfall patterns, while also analysing the factors influencing the adoption and use of weather forecast information in adaptation-decision-making. I used two different theoretical approaches to analyse the research questions: The ‘’Protection Motivation Theory’’ to study how smallholder farmers’ perceptions on the farming vulnerability to changing rainfall patterns shape coping mechanisms and adaptive strategies, and the ‘’Diffusion of Innovations’’ theory to investigate the role of weather forecast information in adaption-decision making. Results indicated that a high level of awareness of climate threats, of the causes of climate change and coping measures, can be important drivers of the adaptation decisions that can contribute to a well-timed anticipation and preparedness against climate threats. The results also suggest that the adoption and use of weather forecast information in farm-decision making depend much on the accuracy and content of information, communication channels, farmers’ digital literacy and forecast skills. The study recommends that the formulation of better adaptation strategies should base their interventions on farmers’ perceptions and knowledge and integrate it with the weather forecast information.